2017
DOI: 10.1111/eth.12593
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs of Sexual Harassment–The Price of Persuasion

Abstract: Females are often subjected to unwanted mating advances from males. Such advances can be costly to both parties. The short‐term costs of harassment to females have been widely explored in the literature; however, few studies have measured the direct fitness costs. Moreover, male costs are seldom considered. Conventional wisdom would lead us to hypothesise that sexual harassment is costly; thus, when males and females are housed together, harassment should reduce foraging, growth and reproductive output and may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We chose to examine challenges and courtship because these are the two mechanisms which can reveal and reinforce the social structure of a group, such as bison (Hawley 1999;Chase 1982;Barroso et al 2000;Marstellar et al 1980;Richards 1974;Rowell 1974). Also, these behaviors cause the most harassment, or are the most likely to cause observable social stress (Creel 2001;Jerry and Brown 2017;Sapolsky 2005;Barroso et al 2000). We found that high ranking members, of both sexes, tended to challenge more, which is consistent with previous studies (Table 1; Reinhardt 1985;Lott 2003;Barroso et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to examine challenges and courtship because these are the two mechanisms which can reveal and reinforce the social structure of a group, such as bison (Hawley 1999;Chase 1982;Barroso et al 2000;Marstellar et al 1980;Richards 1974;Rowell 1974). Also, these behaviors cause the most harassment, or are the most likely to cause observable social stress (Creel 2001;Jerry and Brown 2017;Sapolsky 2005;Barroso et al 2000). We found that high ranking members, of both sexes, tended to challenge more, which is consistent with previous studies (Table 1; Reinhardt 1985;Lott 2003;Barroso et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that mature bulls tend to exert more energy running off suitors (75% of the time they ran) than chasing after females (25%) during observation hours, whereas the young bulls spent their energy running after females (89% of the times they ran). The energy spent by the males during breeding may be costlier than the actual harassment experienced by females (Jerry and Brown 2017). However, the harassment is enough to drive females to stay near higher ranking males, and these males rarely need to run after females in many different locations (Lott 2003;Wolff 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Male harassment can also be costly for males as it has been shown that large male guppies exhibit higher rates of mortality when kept in mixed-sex aquaria (Jerry & Brown 2017) and with both male and female sailfin mollies (Poecilia latipinna) demonstrating a loss of body condition in situations with high levels of male harassment (Makowicz & Schlupp 2013). The costs of male harassment may even have inter-generational effects, as female guppies subject to high levels of harassment produce smaller female offspring and male offspring with shorter gonopodia (Gasparini et al 2012).…”
Section: Male Harassmentmentioning
confidence: 99%